A dataset for anthocyanin analysis in purple-pericarp sweetcorn kernels by LC-DAD-MS - Hong, Hung Trieu (Data Brief, 2020)
This dataset refers to the accompanying article “Optimization of extraction procedure and development of LC-DAD-MS methodology for anthocyanin analysis in anthocyanin-pigmented corn kernels”, published in Food Chemistry [1]. Here, we present concentrations, profiles, MS(2) spectra of individual anthocyanins (including isomers of cyanidin-3-(6’’-malonylglucoside)) of purple-pericarp sweetcorn (PPS) kernels. Furthermore, an additional mass spectrum of an artefact-anthocyanin produced in acidified extraction solutions were reported. This data is further discussed in the accompanying research article [1]. Delphinidin-3-glucoside was used as an internal standard to compensate for individual anthocyanin losses during extraction with acidified solutions. The generated data could be used for anthocyanin identification and quantification in different anthocyanin-containing plant matrices.